PENGARUH TEMPERATUR TERHADAP NILAI SUN PROTECTING FACTOR (SPF) PADA EKSTRAK KUNYIT PUTIH SEBAGAI BAHAN PEMBUAT TABIR SURYA MENGGUNAKAN PELARUT ETIL ASETAT DAN METANOL - Nufus Kanani; Agus Rochmat; Reza Pahlevi; Fitri Yayu Rohani (JURNAL INTEGRASI PROSES, 2017)
White turmeric (Curcuma Mangga) is rhizome that plantyful in Pandeglang Banten, It has not optimally applied. White turmeric is a potential antioxidant that can be used as skin sun screen. The aim of the research is to observe the potential of curcuma manga to be a sunscreen. This study was initially prepared by slicing the rhizome into the small size, after that blanching by adding 0.05% of citric acid into the ryzome, and then followed by exctracting process in different temperature (30;50;70oC). The next one was vaporization solvent (ethyl acetate and methanol) using water bath at 40-45oC and dried at 37oC for 8 hours with oven. The extract was then analyzed by spectrophotometry UV-Vis analysis. The result was then measured show that white turmeric the product potentially used for sun screen. It gave the the highest SPF value about 4.107 of SPF using solvent of ethyl acetate and 3.295 by using methanol solvent. From the GC-MS (Gas Chromathography – Mass Spectro) analysis show that white turmeric contain Oroselone, Xanthone, Curcumin, Calamen, And Palmitic Acid. Key words : antioxidant, White turmeric, Sun Protection Factor (SPF)